KONTEKSTUALISASI PERAN PEREMPUAN DALAM REVOLUSI KARBALA - Y. Sulaeman, Dina (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This paper aims to describe the characters of women in the revolution of Karbala, then synthesize them into a contemporary context, in order to realize a peaceful of religious communities. The findings showed that the incident of Karbala revolution were dominated by the character of women. Sayyidah Zainab, the sister of Imam Hussein, proved able to raise awareness of people with speech techniques in its efforts against the forces of Yazid. The lessons from these events are a spirit and knowledge, that the history often noted female fighters are very dominant, such as her in Karbala revolutions. Hopefully, the women in general can take the wisdom and learning well. With science and her softness, women were able to minimize conflict so as to create a peaceful society as well as religious.